2013
DOI: 10.1007/s12088-013-0411-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Catechol 2,3-Dioxygenase Gene and Construction of a Stable Genetically Engineered Strain for Degrading Crude Oil

Abstract: Pseudomonas putida strain BNF1 was isolated to degrade aromatic hydrocarbons efficiently and use phenol as a main carbon and energy source to support its growth. Catechol 2,3-dioxygenase was found to be the responsible key enzyme for the biodegradation of aromatic hydrocarbons. Catechol 2,3-dioxygenase gene was cloned from plasmid DNA of P. putida strain BNF1. The nucleotide base sequence of a 924 bp segment encoding the catechol 2,3-dioxygenase (C23O) was determined. This segment showed an open reading frame,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 13 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…3). The enzyme C23O is a key enzyme in the degradation of aromatic rings intradiol and extradiol dioxygenase [7] and in the neutralization of petroleum-based compounds [4], thereby, breaking down the toxic compounds in the crude oil into harmless chemicals. The screening for the C23O gene in bacteria further authenticates their involvement in the degradation of crude oil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). The enzyme C23O is a key enzyme in the degradation of aromatic rings intradiol and extradiol dioxygenase [7] and in the neutralization of petroleum-based compounds [4], thereby, breaking down the toxic compounds in the crude oil into harmless chemicals. The screening for the C23O gene in bacteria further authenticates their involvement in the degradation of crude oil.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the transformants bearing the correct inserts from the selected clones, colony PCR was performed in 96 wells PCR plates using M13 primers [4]. Each 25 μl reaction mixture contained 0.5U Taq polymerase enzyme, 1X PCR buffer, 0.4 pmol primers and 0.2 mM of each dNTP.…”
Section: Identification Of True Transformantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of intermediates detected during fluoranthene degradation suggests that both ortho-and meta-cleavage pathways were active in the consortium (and postulated in Figure S2), which might be due to the presence of catechol dioxygenases genes in all the three strains. The previous studies have reported the presence of catechol dioxygenases genes in Mycobacterium, Pseudomonas and Burkholderia (Kang et al 2016;Xie et al 2014;Suzuki et al 2002;Lopez et al 2005;Cenci et al 1999;Juhasz et al 1997).…”
Section: Stoichiometry Profile Of Fluoranthene Degradationmentioning
confidence: 95%
“…BS3 was developed with insertion of xylE gene encoding for catechol 2,3-dioxygenase enzyme from Pseudomonas putida strain BNF1 responsible for biodegradation of hydrocarbons, which are aromatic in nature. This engineered strain expressed enzyme with broad substrate specificity, hence exhibiting a superior efficacy to degrade a variety of n-alkanes and other aromatic hydrocarbons when compared to its wild strain [ 94 ]. Engineered psychrophilic recombinant Antarctic Pseudoalteromonas haloplanktis TAC125 successfully expressed toluene-o-xylene monooxygenase (capable of degrading a wide range of aromatics) along with its inherent laccase-like protein to address the remediation of cold and marine xenobiotic loaded effluents [ 95 ].…”
Section: Bioengineering Of Microorganisms For Soil Health Restoration By Remediationmentioning
confidence: 99%